Multiple Pathway–Mediated Gut-Modulatory Effects of Maerua subcordata (Gilg) DeWolf - Palla AH; Sibhat GG; Karim A; Rehman NU; Hiben MG (Dove Medical Press, 2020)
Amber Hanif Palla,1 Gereziher Gebremedhin Sibhat,2 Aman Karim,2 Najeeb Ur Rehman,3 Mebrahtom Gebrelibanos Hiben2 1Department of Basic Medical Sciences, Faculty of Pharmacy, Barrett Hodgson University, Karachi, Pakistan; 2Department of Pharmacognosy, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 3Department of Pharmacology and Toxicology, College of Pharmacy, Prince Sattam Bin Abdulaziz University, Al-Kharj 11942, Saudi ArabiaCorrespondence: Mebrahtom Gebrelibanos HibenMekelle University, PO Box 1871 Tel +251 91-118-3120Fax + 251-34-441-66-81/40-93-04Email mmgshn@gmail.comBackground: Gastrointestinal disorders are often poorly managed, especially in developing countries, where there are limited resources and therapeutic options. Despite the rich diversity of medicinal plants that offer effective treatment options with fewer side effects, studies that provide scientific verification are lacking. Maerua subcordata (Gilg) DeWolf is among the plants claimed to have wide traditional medicine, use, including as a remedy against gastrointestinal problems. Therefore, this work aimed to evaluate the gut-modulatory effects of a crude leaf extract of M. subcordata (MSL.Cr), as well as its possible mechanism of action.Methods: A castor oil (10 mL/kg)–induced diarrheal mouse model was used to evaluate the antidiarrheal effect of MSL.Cr, and the spasmodic/antispasmodic effect of the extract was assessed using isolated rabbit jejunum with and without addition of standard cholinergic agonists/antagonists to predict the possible mechanism of action.Results: MSL.Cr exhibited 40% and 80% protection against castor oil–induced diarrhea in mice at doses of 500 and 1,000 mg/kg, respectively. In isolated rabbit jejunum, the extract increased spontaneous contractions at low doses (0.01– 0.1 mg/mL), and was sensitive to atropine, whereas it showed complete inhibition at higher doses (0.3– 1 mg/mL). It was shown that the relaxant effect was possibly mediated by the involvement of phosphodiesterase-enzyme inhibition and K+-channel activation. The extract potentiated the control concentration–response curve of carbachol, shifting it to the left, similarly to the control drug papaverine. The potassium-channel opening–like activity of MSL.Cr was possibly mediated by the involvement of aspecific K+-channels inhibition, since tetraethylammonium, anunselective antagonist of K+ channels, significantly reversed its inhibitory effect.Conclusion: This study showed that the M. subcordata leaf extract demonstrated gut-modulatory effects, possibly mediated by a combination of muscarinic-receptor stimulation, phosphodiesterase inhibition, and aspecific K+-channel activation.Keywords: Maeruaa subcordata, constipation, diarrhea, phosphodiesterase inhibition, K+ channel activation